Interpreting art in museums and galleries - Whitehead, Christopher, 1972- (Routledge, 2012)
In this carefully focused book, Christopher Whitehead presents both a study of and guide to curatorial practices of art interpretation, including the manipulation of the physical display environment and the production of supporting materials, from text panels to audioguides and interactives.